Verification of the multi-layer SNOWPACK model with different water transport schemes - Wever, Nander; Schmid, Lino; Heilig, Achim; Eisen, Olaf; Fierz, C.; Lehning, M. (The Cryosphere discussions, 2015)
The widely-used detailed SNOWPACK model has undergone constant - development over the years. A notable recent extension is the - introduction of a Richards Equation (RE) solver as an alternative for - the bucket-type approach for describing water transport in the snow and - soil layers. In addition, continuous updates of snow settling and new - snow density parametrisations have changed model behaviour. This study - presents a detailed evaluation of model performance against a - comprehensive multi-year data set from Weissfluhjoch near Davos, - Switzerland. The data set is collected by automatic meteorological and - snowpack measurements and manual snow profiles. During the main winter - season, snow height (RMSE: <4.2 cm), snow water equivalent (SWE, - RMSE: <40 mm w.e.), snow temperature distributions (typical deviation - with measurements: <1.0 °C) and snow density (typical deviation - with observations: <50 kg m-3) as well as their temporal - evolution are well simulated in the model and the influence of the two - water transport schemes is small. The RE approach reproduces internal - differences over capillary barriers but fails to predict enough grain - growth since the growth routines have been calibrated using the bucket - scheme in the original SNOWPACK model. The agreement in both density and - grain size is sufficient to parametrise the hydraulic properties. In the - melt season, a more pronounced underestimation of typically 200 mm w.e. - in SWE is found. The discrepancies between the simulations and the field - data are generally larger than the differences between the two water - transport schemes. Nevertheless, the detailed comparison of the internal - snowpack structure shows that the timing of internal temperature and - water dynamics is adequately and better represented with the new RE - approach when compared to the conventional bucket scheme. On the - contrary, the progress of the meltwater front in the snowpack as - detected by radar and the temporal evolution of the vertical - distribution of melt forms in manually observed snow profiles do not - support this conclusion. This discrepancy suggests that the - implementation of RE partly mimics preferential flow effects.
Gesehen am 30.06.2020